Analisis Manajemen Pembiayaan dalam Meningkatkan Efektivitas Pembelajaran Siswa SDN 235 Lengkong Kecil - Suharyanto H. Soro; Ahmad Rifandi; Winna Islamiyathi; Veranita Intan Palupy (LP. Ma'arif Janggan Magetan, 2024)
Financing management in the world of education is an important element in improving the quality of graduates. Financing activities are carried out based on needs, both internal and external needs. In other words, learning activities experience obstacles and problems if financial support does not match the needs of the educational unit. This research aims to exploit financing management in improving the effectiveness of the learning quality of students at SDN 235 Lengkong Kecil. Researchers use a qualitative research paradigm. Data collection methods use observation, interviews and documentation studies. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The sample in this study was the school principal, treasurer, BOS fund operator, teachers and committee chair of SDN 235 Lengkong Kecil. The research results show that: (1) Financing management is carried out according to procedures involving all stakeholders so that it is transparent through readability of education quality reports, (2) Financing management is carried out professionally so that it can increase the effectiveness of learning quality. In other words, through proper financing management, school facilities and infrastructure are met according to the needs of the learning process so that school financing management has a positive impact on the efficiency and effectiveness of the quality of learning.